Developing Models to Explain Point Spread of NCAA Women’s Division II Basketball Games - Huang, Feifei; Magel, Rhonda (Journal of Advance Research in Mathematics and Statistics (ISSN 2208-2409), 2016)
A model is developed using in-game statistics to help explain the final point spread of a Women’s Division II Basketball Tournament game. A model is also developed to estimate the probability of a team winning the game given significant in-game statistics. Both of the models are verified based on a random sample of basketball games that were not used in the development of the models. The models were then used to predict the outcomes of the 63 games played in the 2015 NCAA Division II Women’s Basketball tournament replacing the actual in-game statistics with seasonal averages of the corresponding statistics. Results are given.